Pengaruh Latihan Senam Kegel Terhadap Inkontinensia Urine Pada Lansia Di RS Toeloengredjo Pare - Sulistyawati, Aulia Ika; Abdullah, Ahmad; Kasimbara, Rachma Putri; Fau, Yohanes Deo (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective Â The purpose of this study was to determine the effect of Kegel exercises on urinary frequency in elderly patients at the Geriatrics Polyclinic, Toeloengredjo Hospital.Methods: This article Â This type of research was conducted using the